Hsa-miR-607, lncRNA TUG1 and hsa_circ_0071106 can be combined as biomarkers in type 2 diabetes mellitus. Issue 18 (September 2022) - Su, Manna; Yu, Tongxin; Yu, Yongji; Cheng, Qiuting; Zheng, Yingying; Liao, Rifang; Zeng, Zhuanping
Type 2 diabetes mellitus (T2DM) is a multifactorial disorder that leads to alterations in gene regulation. ncRNAs have the characteristics of tissue specificity, disease specificity, timing specificity, high stability and post transcriptional regulation effect. These preconditions are more conducive to promote ncRNA to become a new biomarker for clinical diagnosis. Our study aims to explore the relationship between circRNA, lncRNA, miRNA and T2DM, and to evaluate their diagnostic value for T2DM. A total of 101 pairs of T2DM and controls were conducted in the study. QRT-PCR was used to study the differential expression of circRNAs, miRNAs and lncRNAs. ROC curve was used to estimate their diagnostic value in T2DM. Compared with healthy controls, the expression levels of hsa_circ_0071106, hsa_circ_0000284, hsa_circ_0071271, hsa-miR-29a-5p, hsa-miR-3690, hsa-miR-607, lncRNA MEG3 and lncRNA TUG1were higher in T2DM (all P  < 0.05). The AUCs of hsa_circ_0071106, hsa-miR-607 and lncRNA TUG1 for diagnosis of T2DM were 0.563, 0.645 and 0.642, respectively. The combined AUC of hsa-miR-607, lncRNA TUG1 and hsa_circ_0071106 was 0.798 ([0.720~0.875], P  < 0.001). Moreover, the sensitivity of combined diagnosis was 75.2% and the specificity was 100.0%. The levels of lncRNA TUG1, hsa-miR-607 and hsa_circ_0071106 in peripheral blood have potential clinical diagnostic value for T2DM.